Genome-wide identification of Cymbidium sinense WRKY gene family and the importance of its Group III members in response to abiotic stress - Wei, Yong-Lu; Jin, Jian-Peng; Liang, Di; Gao, Jie; Li, Jie; Xie, Qi; Lu, Chu-Qiao; Yang, Feng-Xi; Zhu, Gen-Fa (Frontiers in Plant Science, 2022)
Transcription factors (TFs) of the WRKY family play pivotal roles in defense responses and secondary metabolism of plants. Although WRKY TFs are well documented in numerous plant species, no study has performed a genome-wide investigation of the WRKY gene family in Cymbidium sinense. In the present work, we found 64 C. sinense WRKY (CsWRKY) TFs, and they were further divided into eight subgroups. Chromosomal distribution of CsWRKYs revealed that the majority of these genes were localized on 16 chromosomes, especially on Chromosome 2. Syntenic analysis implied that 13 (20.31%) genes were derived from segmental duplication events, and 17 orthologous gene pairs were identified between Arabidopsis thaliana WRKY (AtWRKY) and CsWRKY genes. Moreover, 55 of the 64 CsWRKYs were detectable in different plant tissues in response to exposure to plant hormones. Among them, Group III members were strongly induced in response to various hormone treatments, indicating their potential essential roles in hormone signaling. We subsequently analyzed the function of CsWRKY18 in Group III. The CsWRKY18 was localized in the nucleus. The constitutive expression of CsWRKY18 in Arabidopsis led to enhanced sensitivity to ABA-mediated seed germination and root growth and elevated plant tolerance to abiotic stress within the ABA-dependent pathway. Overall, our study represented the first genome-wide characterization and functional analysis of WRKY TFs in C. sinense, which could provide useful clues about the evolution and functional description of CsWRKY genes.